The impact of the arrival of different groups of tourists by country of origin to the scope of tourist visits in Rogaška Slatina between 1953 and 2012 - Horvat, Uroš (Journal for Geography, 2013)
The paper discusses the scope of tourist visits in Rogaška Slatina (one of the oldest and the most important tourist places and spas in Slovenia) in connection with of the arrival of different groups of tourists by the country of origin. It has been found that the tourist visits all the time depends on the influx of tourists from just a few countries. Changes in tourist flows consequently has major impact on the scope of tourist visits and its characteristics. Throughout the period, the majority of tourists in the resort came from abroad. Period until the end of the 1980s were marked mostly by tourists from other republics of the former Yugoslavia and Austria, the second half of the 1990s and since 2000 with tourists from Italy and after 2010, from the Russian Federation. Tourists from Slovenia were the most important group of tourists only the 1990s, in the period of the greatest crisis in the development of the health resort.
Keywords: tourism; foreign tourist; average length of tourist stay; health resort; spa; Rogaška Slatina; Slovenia